Identification and Analysis of Amino Acid Mutations in Porin IB That Mediate Intermediate-Level Resistance to Penicillin and Tetracycline in Neisseria gonorrhoeae - Olesky, Melanie (American Society for Microbiology, 2002)
PenB is the third resistance determinant in the stepwise acquisition of multiple resistance genes in chromosomally mediated resistant Neisseria gonorrhoeae (CMRNG). Alterations in por(IB), one of two alleles at the por locus that encodes the outer membrane protein porin IB (PIB), were recently reported to be responsible for the increased resistance to penicillin and tetracycline conferred by penB, but the specific mutations conferring antibiotic resistance were not identified experimentally. To determine which amino acids in PIB confer increased resistance, we transformed a recipient strain with chimeras of the por(IB) genes from strains FA1090 and FA140 (penB2). These studies revealed that two amino acid changes, G120D and A121D, were both necessary and sufficient to confer increased resistance to penicillin and tetracycline. Site-saturation and site-directed mutagenesis of Gly-120 and Ala-121 revealed that both a single mutation, G120K, and the double mutations G120R A121H and G120P A121P also conferred antibiotic resistance to the recipient strain. The identical mutations in PIA increased penicillin and tetracycline resistance either moderately or not at all. Analysis of por(IB) genes present in the GenBank database from 51 clinical isolates demonstrated that lysine and aspartate mutations at positions 120 and/or 121 also occur in nature. These studies demonstrate that charged amino acids at positions 120 and 121 in PIB are highly preferential for conferring resistance to penicillin and tetracycline in N. gonorrhoeae.